Komunikasi Lintas Budaya Generasi Milenial dalam Melestarikan Budaya Berkebaya - Risya Hasna Masytah; Kiki Zakiah (Bandung Conference Series: Public Relations, 2024)
Abstract. Kebaya culture is an important part of the cultural identity of a country or region, and understanding the values and meaning behind kebaya can help the millennial generation appreciate and preserve this cultural heritage. To preserve and introduce the culture of wearing kebaya to the community, a community called Wanita Berbaya Indonesia was formed. As a fashion influencer and Indonesian Kebaya Women activist, the owner of the Moja Rasya Instagram account always shares various references regarding her kebaya clothing. This is done as a form of communication to the millennial generation so that the kebaya culture can continue to be preserved.The focus of the research is analyzing cross-cultural communication of the millennial generation in preserving kebaya culture, using descriptive qualitative research methods using an ethnographic approach. To reveal how cross-cultural communication of the millennial generation is in preserving kebaya culture.Based on research results, several followers of the Moja Rasya Instagram account stated that the cross-cultural communication carried out by him with the millennial generation so that the kebaya culture could continue to be preserved had run optimally. Abstrak. Budaya berkebaya adalah bagian penting dari identitas budaya suatu negara atau daerah, dan pemahaman terhadap nilai-nilai dan makna di balik berkebaya dapat membantu generasi milenial menghargai dan melestarikan warisan budaya tersebut. Untuk melestarikan dan mengenalkan budaya berkebaya kepada masyarakat, dibentuklah sebuah komunitas bernama Perempuan Berkebaya Indonesia. Sebagai seorang fashion influencer dan juga penggiat Perempuan Berkebaya Indonesia, pemilik akun instagram Moja Rasya selalu membagikan berbagai referensi mengenai pakaian berkebaya miliknya. Hal tersebut dilakukan sebagai bentuk komunikasi kepada generasi milenilai agar budaya berkebaya dapat terus dilestarikan.Fokus penelitian menganalisis komunikasi lintas budaya generasi milenial dalam melestarikan budaya berkebaya, menggunakan metode penelitian kualitatif deskriptif dengan menggunakan pendekatan etnografi. Untuk mengungkapkan bagaimana komunikasi lintas budaya generasi milenial dalam melestarikan budaya berkebaya. Berdasarkan hasil penelitian b ahwa beberapa pengikut dari akun instagram Moja Rasya, bahwa komunikasi lintas budaya yang dilakukan olehnya terhadap generasi milenial agar budaya berkebaya dapat terus dilestarikan telah berjalan secara optimal.